Education in Lithuanian schools of Soviet Byelorussia in 1930s and 40s - Prėskienis, B. (Psichologija, 1977)
The number of Lithuanians was some 7000 in Soviet Byelorussia in 1926. Their absolute majority was concentrated in villages. The party and Soviet organs of Byelorussia provided favourable conditions for national minorities to receive instruction in their native language. Schools for Lithuanians were set up, adults were taught, text-books were published, the teaching personnel was trained. Non-class activities were extensive and diversified. The Lithuanian national sector of the Academy of Sciences of the Byelorussian SSR analysed Lithuania’s history, culture and ethnography. These and other forms of educational and cultural work are dealt with in the article. The setting up of Lithuanian schools other forms of educational and cultural work obviously demonstrate the realization of Leninist national policy into practice.